Long term lymphocyte reconstitution after alemtuzumab treatment of multiple sclerosis. Issue 3 (5th November 2011) - Hill-Cawthorne, Grant A; Button, Tom; Tuohy, Orla; Jones, Joanne L; May, Karen; Somerfield, Jennifer; Green, Alison; Giovannoni, Gavin; Compston, D Alastair S; Fahey, Michael T; Coles, Alasdair J
Abstract : Background: Alemtuzumab is a lymphocyte depleting monoclonal antibody that has demonstrated superior efficacy over interferon β-1a for relapsing–remitting multiple sclerosis (MS), and is currently under investigation in phase 3 trials. One unresolved issue is the duration and significance of the lymphopenia induced. The long term effects on lymphocyte reconstitution of a single course, and the consequences that this has on disability, morbidity, mortality and autoimmunity, were examined. Methods: The lymphocyte reconstitution (n=36; 384 person years) and crude safety data (n=37; 447 person years) are reported for the first patients with progressive MS to receive alemtuzumab (1991–1997). Reconstitution time was expressed as a geometric mean or, when a non-negligible number of individuals failed to recover, as a median using survival analysis. Results: Geometric mean recovery time (GMRT) of total lymphocyte counts to the lower limit of the normal range (LLN; ≥1.0×10 9  cells/l) was 12.7 months (95% CI 8.8 to 18.2 months). For B cells, GMRT to LLN (≥0.1×10 9 /l) was 7.1 months (95% CI 5.3 to 9.5); median recovery times for CD8 (LLN ≥0.2×10 9  cells/l) and CD4 lymphocytes (LLN ≥0.4×10 9  cells/l) were 20 months and 35 months, respectively. However, CD8 and CD4 counts recovered to baseline levels in only 30% and 21% of patients, respectively. No infective safety concerns arose during 447 person years of follow-up. Conclusions: Lymphocyte counts recovered to LLN after a single course of alemtuzumab in approximately 8 months (B cells) and 3 years (T cell subsets), but usually did not recover to baseline values. However, this long lasting lymphopenia in patients with a previously normal immune system was not associated with an increased risk of serious opportunistic infection.